THE EFFECT BRAIN GYM TO FINE MOTOR DEVELOPMENT ON PRE SCHOOL CHILDREN - Desy Siswi Anjar Sari; Fitri Firranda Nurmalisyah (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Pre-school is a golden period in the development process. It consist of cognitive, physical, motoric, and psychosocial aspects of a child developing optimally. One of the developmental parameters is fine motor, its related to physical skills that involve the muscles of the fingertips and eye-hand coordination. The aim was to analyse the effect of brain gymn to improve fine motoric design. The design was a one-group pre-experimental with pre-posttest. The population was all students pre school in Sentul Jombang, East Java. Total sample were 33 respondents which matched the inclusion and exclusion criteria. The data collected by questionnaire sheets were adopted from instrument for assessing child development, namely KPSP. Intervention was given by brain exercise were carried out 3 times a week for 2 months then analyzed using Wilcoxon with a significance value of α = 0.05. The results showed that brain exercise in pre-school children was able to improve fine motor  skills (p = 0.000). Brain gym is one of the effective ways to improve fine motor skills in children because being able to facilitate blood flow and oxygen to the brain also helps overall brain development. Therefore, brain gym is highly recommended for pre-school children.